Estudo farmacognóstico de Pithecoctenium echinatum (Jacq.) Baill - Casoti, Rosana (2012)
Pithecoctenium echinatum belongs to the family Bignoniaceae, popularly known as comb monkey used in folk medicine for inflammations, rheumatism, skin infections, headaches, cleanses the blood and calming. The objective of this study was to characterize morphological and anatomical fruit of P. echinatum; to determine the physico-chemical quality of the plant drug, isolating chemical compounds of secondary metabolism, as well as to investigate antimicrobial, antioxidant and anti-inflammatory, and analyzing biochemical parameters of liver and kidney toxicity in the crude extract (CE) of seeds of P. echinatum. This species has bicarpelar ovary with the presence of trichomes, crystals and emergencies. It has parietal placentation. The rudiment seminal anatropous, unitegmic and tenuinucellate. The ring nectary has stomatal complexes and trichomes. The epicarp has cutin with the presence of lenticels, estomatíferos and complex emergencies. The outer mesocarp has parenchyma cells, stone cells, sclerified cells and crystals. The endocarp is represented by a single cell layer is not sclerified. The seed is winged and exotestal. The endothelium and the endosperm are the membranaceous embryo. The mesophyll has chemical compounds such as alkaloids, fixed oils, volatile oils, scarce presence of starch and consists of pectic walls. In physico-chemical characterization, using pharmacopoeia tests was used dried vegetable drug, noting that no significant variation of the samples collected in different locations. The hydroethanolic extract 70% seeds of P. echinatum presented secondary metabolic compounds such as steroids and/or triterpenes, flavonoids, alkaloids, anthraquinones, tannins, catechin, phenolic hydroxyl heterosides cardiotonic and volatile oils. Assay polyphenols, flavonoids and tannins were determined by spectroscopic in the CE and fractions. P. echinatum showed antioxidant potential (IC50 131.84 mg/ml) in acetate fraction by the DPPH method and antimicrobial activity to P. aeruginosa, P. zophii and C. albicans by the microdilution method (MIC). From the CE the seeds of P. echinatum we performed the isolation and identification of hesperetin and diometin. These flavonoids were isolated from P. echinatum first. The compounds were determined and analyzed by HPLC / MS and NMR and their spectra compared with the literature. The anti-inflammatory activity of the CE was assayed by the induction of inflammation for cotton rolls and serum taken from rats submitted to the bioassay, in which were administered orally by 300mg/kg/day of CE for 6 consecutive days and compared to nimesulide (5mg/kg/day) and negative control (propylene glycol 20% v/v). The results showed that the CE of P. echinatum showed significant inhibition of inflammation of 24.7%, similar to the inhibition obtained by the group of animals treated with nimesulide 21.4% compared to controls. The hematological parameters showed an increase in the number of leukocytes and decreased of corpuscular medium volume, while AST, ALT and creatinine showed no significant difference in the use of CE compared with the control group propylene glycol. Therefore, the physico-chemical parameters established for P. echinatum enable quality control of drugs of this kind, and this presented antimicrobial, antioxidant and anti-inflammatory activities. Furthermore, no evidence of a hepatotocidade and nephrotoxicity in the experimental conditions tested.